IMPLEMENTASI KEBIJAKAN CORE VALUES DAN EMPLOYER BRANDING APARATUR SIPIL NEGARA BERDASARKAN SURAT EDARAN MENTERI PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI NOMOR 20 TAHUN 2021 DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN REMBANG - Arthania, Athaya Arla; Nurcahyanto, Herbasuki; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
As the development of public services has required all ASNs to continue to improve their performance in order to meet the needs of the community. For this reason, all ASN are required to always be guided by a work culture that refers to Pancasila in order to prevent behavioral deviations. Since 2021, the Minister for Empowerment of State Apparatus and Bureaucratic Reform has issued a new policy regarding ASN Core Values and Employer Branding which requires all ASNs in Indonesia to be able to implement it from the central to the regional level. The locus of this research is at the Rembang Regency DPRD Secretariat. This research aims to analyze the implementation of Core Values and Employer Branding policies for state civil servants based on the Circular Letter of the Minister for Administrative Reform and Bureaucratic Reform Number 20 of 2021 at the Secretariat of the Rembang Regency Regional People's Representative Council as well as supporting and inhibiting factors. The method used in this research is qualitative with interviews as the instrument. The respondents were 5 employees who worked at the Rembang Regency DPRD Secretariat office, especially those related to the implementation of Core Values and ASN Employer Branding policies. The research results show that the implementation of the ASN Core Values and Employer Branding policies has gone well, marked by an impact on the organization, change and acceptance by the organization. However, it is still hampered by employee competency, infrastructure, budget systems and employee discipline that are not yet optimal. Researchers provide recommendations for the DPRD Secretariat to reform of All Civil Servant, infrastructure, budget systems and strengthening work rules.